Effectiveness of Flashing Brake and Hazard Systems in Avoiding Rear-End Crashes. (20th January 2014) - Li, Guofa; Wang, Wenjun; Li, Shengbo Eben; Cheng, Bo; Green, Paul
Abstract : Three experiments were conducted to examine the effectiveness of two forward crash warning systems, a flashing brake system and a flashing hazard system, using an advanced driving simulator. In Experiment 1, 20 subjects followed a lead vehicle with a desired time gap and braked when necessary. Results showed that time gap, velocity, and deceleration of the lead vehicle all significantly affected drivers' brake response times. In Experiment 2, six brake response times to a sudden lead vehicle deceleration (0.6 g at 80 km/h) were measured for six time gaps. Results showed that flashing brake system and flashing hazard system reduced drivers' brake response times by 0.14 0.62 s and 0.03 0.95 s, respectively, in the various situations tested. The effects of flashing color and illuminated size on drivers' brake response times were examined in Experiment 3. Results showed that flashing amber lamps reduced drivers' brake response times significantly by 0.11 s (10%) on average compared with red lamps. These findings demonstrate the effectiveness of both flashing systems in reducing drivers' brake response times in urgent situations and may warrant further consideration by manufacturers.